Analisis Strategi Perencanaan Mutu Satuan Pendidikan di Lembaga Pendidikan Islam di Indonesia - Mizanul Hasanah; Priatna Sandy; Mahmud Mannan; July Amalia Nasucha (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This article originates from the author's anxiety over educational problems that are still a terrible scourge for the Indonesian people, namely the low quality of education at every level and educational unit. Various indicators of the quality of education have not shown any improvement, especially in the education units in Islamic educational institutions. Madrasah is an Islamic educational institution that was created among Indonesian people as a result of the transformation of culture and religious values. This type of research is a literature study. The data obtained comes from teaching materials, including books, publication journals, thesis repositories, holy of Qur'an and Hadish, and other types of scientific work. The author's goal is to analyze what the strategies are for improving the quality of education in Indonesia, to analyze planning at each level of educational units in Indonesia, and to analyze the problems and solutions of educational institutions in Indonesia. Basically, it is aimed at preparing humans to face a more prosperous future, both individual’s and collectively as a society, nation, and world.